Development of e-modul based on three-dimensional thinking graph to improve critical reasoning of junior high school students - Ulin Nuha; Aulia Rizky Nur Cahyani; S. Supeno; R. Rusdianto; Diah Wahyuni; Rizka Elan Fadhilah (Universitas Muhammadiyah Malang, 2024)
The process of strengthening character education in Indonesia is encapsulated in the initiative to enhance the Profil Pelajar Pancasila, with critical reasoning being one of its key dimensions. In the context of science education, critical reasoning involves engaging students in the development and testing of hypotheses. This study aims to evaluate the validity, practicality, and effectiveness of an e-module designed based on three-dimensional thinking graphs, intended to enhance critical reasoning among junior high school students in science learning. The research employs the ADDIE development model, with data collected through observation, interviews, tests (pretest and posttest), validation sheets, student response questionnaires, and implementation observation sheets. Results indicate that the e-module is highly valid, with a 93% validation score from experts, practical according to both observers (93%) and student responses (84.4%), and moderately effective, with an effectiveness score of 0.62. These findings suggest that the three-dimensional thinking graph-based e-module is a suitable tool for improving critical reasoning in the science learning process.